PERBANDINGAN RESPON NYERI ANAK USIA TODDLER DAN PRASEKOLAH YANG DILAKUKAN PROSEDUR INVASIF - Sada Ulina Sembiring; Riri ' Novayelinda; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to compare the pain response of toddler and preschool children during invasive procedures. The design of this study was cross-sectional. The sample of this study was 26 respondents which were divided into 13 toddlers and 13 preschoolers by using purposive sampling technique with inclusion criteria. Measuring instruments of this research used FLACC (Facial, Legs, Activity, Cry, Consolability) scale for behavioral response and the physiological response based on heart rate and respiratory rate of children. This study was analyzed using independent sample T test. The statistical results of behavioral pain responses using FLACC scale was obtained p value (0.000) < alpha (0.05), so that it can be concluded that there was difference in behavioral responses pain between toddler and preschool children. Statistical test results of  heart rate was obtained p value (0.000) < alpha (0.05) and respiratory rate was obtained p value (0.028) < alpha (0.05), so that it can be concluded that there were a difference in the heart rate and respiratory rate between toddler and preschool children after invasive procedures. The study recommends for health workers in order to do behavioral responses pain management for toddler and preschool children during invasive procedures. Key words: FLACC, heart rate, pain response, respiratory rate